Epigenetic changes modulate schistosome egg formation and are a novel target for reducing transmission of schistosomiasis. - Vitor Coutinho Carneiro (Public Library of Science (PLoS), 2014)
Treatment and control of schistosomiasis relies on the only available drug, praziquantel, and the search for alternative chemotherapeutic agents is therefore urgent. Egg production is required for the transmission and immunopathology of schistosomiasis and females of S. mansoni lay 300 eggs daily. A large fraction of the total mRNA in the mature female worm encodes one eggshell protein, Smp14. We report that the nuclear receptors SmRXR1 and SmNR1 regulate Smp14 transcription through the recruitment of two histone acetyltransferases (HATs), SmGCN5 and SmCBP1. The treatment of HEK293 cells with histone deacetylase (HDAC) inhibitors (NaB or TSA) produced an 8-fold activation of the SmRXR1/SmNR1-mediated Smp14 promoter activity. Incubation with synthetic HAT inhibitors, including PU139, significantly impaired the Smp14 promoter activity in these cells. Worm pairs cultivated in the presence of PU139 exhibited limited expression of Smp14 mRNA and protein. ChIP analysis demonstrated chromatin condensation at the Smp14 promoter site in worms treated with PU139. ChIP also revealed the presence of H3K27me3 and the absence of RNA Pol II at the Smp14 promoter region in the PU139-treated worms. Most significantly, the PU139-mediated inhibition of Smp14 expression resulted in a significant number of abnormal eggs as well as defective eggs within the ootype. In addition, scanning electron microscopy revealed structural defects and unformed eggshells, and vitelline cell leakage was apparent. The dsRNAi-targeting of SmGCN5 or SmCBP1 significantly decreased Smp14 transcription and protein synthesis, which compromised the reproductive system of mature female worms, egg-laying and egg morphology. Our data strongly suggest that the inhibition of Smp14 expression targeting SmGCN5 and/or SmCBP1 represents a novel and effective strategy to control S. mansoni egg development.